Pan-cancer and single-cell analysis reveals FAM83D expression as a cancer prognostic biomarker - Yu, Haiyang; Chen, Qinhao; Wang, Ziming; Qian, Xiaojun; Pan, Yueyin (Frontiers in Genetics, 2022)
Background: The family with sequence similarity 83 member D (FAM83D) protein is known to play a significant role in many human diseases. However, its role in cancer remains ambiguous. This study aimed to investigate the function of FAM83D in a pan-cancer analysis, with a special focus on breast cancer. Methods: Samples were collected from The Cancer Genome Atlas (TCGA) and used for bioinformatic analysis. Datasets from the Gene Expression Omnibus (GEO) and Genotype-Tissue Expression (GTEx) databases were also analyzed for verification. The potential value of FAM83D as a prognostic and diagnostic biomarker was visualized through R software. The"survival" and "GSVA" package were used for univariate, multivariate and pathway enrichment analyseis. We further analyzed the CancerSEA databases and TISIDB websites for single-cell and immune-related profiling. Lastly, we validated those data in vitro using quantitative reverse transcriptase-polymerase chain reaction (RT‒qPCR), cell counting kit-8 (CCK-8), transwell, flow cytometry, and tumorigenicity assays in a murine cell line model. Results: The expression of FAM83D in tumor samples was significantly higher than in normal tissues for most cancer types in the datasets. We confirmed this finding using RT‒qPCR in a breast cancer cell line. Analysis of multiple datasets suggests that overall survival (OS) was extremely poor for breast cancer patients with high FAM83D expression. The CCK-8 assay demonstrated that MCF-7 cell proliferation was inhibited after genetic silencing of FAM83D. Transwell assay showed that knockdown of FAM83D significantly inhibited the invasion and migration ability of MCF-7 cells compared to the control. The results of flow cytometry showed that silencing FAM83D could block the G1 phase of MCF-7 cells compared with negative groups. The tumorigenicity assay in nude mice indicated that the tumorigenic ability to silence FAM83D decreased compared. Conclusions: Results suggest that FAM83D expression can serve as a valuable biomarker and core gene across cancer types. Furthermore, FAM83D expression is significantly associated with MCF-7 cell proliferation and thus may be a prospective prognostic biomarker especially for breast cancer.